2017
DOI: 10.1016/j.juro.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Urinary Retention is an Independent Predictor of Short-Term and Long-Term Future Bladder Outlet Procedure in Men

Abstract: In men 60 years old or older postoperative urinary retention identified those with an increased incidence of bladder outlet procedures within 3 years. Men younger than 60 years had a low rate of subsequent bladder outlet procedures regardless of a postoperative urinary retention diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Urinary retention is a prevalent clinical condition representing the reason for urology referral in 5%-25% of cases [8,9]. In our series, 5% of all urological consultations (inpatient and outpatient) were conducted due to POUR which is one of the main indications for bladder catheterization [10].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Urinary retention is a prevalent clinical condition representing the reason for urology referral in 5%-25% of cases [8,9]. In our series, 5% of all urological consultations (inpatient and outpatient) were conducted due to POUR which is one of the main indications for bladder catheterization [10].…”
Section: Discussionmentioning
confidence: 75%
“…At 29 months follow-up, 1.855 (0.24%) patients underwent a bladder outlet procedure due to persistent urinary retention. They concluded that POUR after non-urological surgery increased the likelihood of a bladder outlet procedure within three years [8]. In our study, patients who underwent bladder outlet procedures during follow-up were excluded.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…POUR contributes to increased health care costs and is associated with decreased patient satisfaction. 6,[8][9][10][11][12] Risks associated with indwelling urinary catheterization, such as catheter-associated uri- nary tract infections (CAUTI), contribute to significant mortality and morbidity. Over 13 000 deaths each year in the United States are associated with urinary tract infections, and CAUTIs can potentially progress to sepsis and endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Morbidities include urinary tract infection, sepsis, bladder distension requiring self-catheterization, kidney injury, increased length of stay (LOS), wound infection, and venous thromboembolism. [10][11][12] POUR is also associated with decreased patient satisfaction. 8 A literature review identified early ambulation, early removal of indwelling catheters, and prophylactic tamsulosin as effective measures for preventing POUR.…”
mentioning
confidence: 99%